Description of the previously unknown tadpole of Hyalinobatrachium pulveratum (Anura: Centrolenidae) - Hoffmann, Heinz (2004)
Egg clutches of the centrolenid Hyalinobatrachium pulveratum were sampled in four lowland loca- tions of Costa Rica. The ontogenesis of the tadpoles of this species is documented by periodical descriptions of the larval stages. Larvae of H. pulveratum change their shape during development because of the non-equal growth of some body parts. Due to these changes the larvae in early stages of development differ considerably to those from later stages. Young larvae have a nearly circular cross-section, whereas later larval stages change to a typical flat shape. Some further morphological characteristics like width of the interorbital distance and the oral disk width change but not proportional to larvae length. Numerous measurements on different larval sizes help to recognize the larvae of H. pulveratum in all stages. The striking bright red hyobranchial sinus is the con- spicuous characteristic feature ventrally of the hyobranchial apparatus. The use of allometric values for taxo- nomic and ontogenetic studies is discussed.